Scarring effects of the first labor market experience - Oskar Nordström Skans (Institute for the Study of Labor (IZA), 2011)
The paper studies the relationship between teenagers' first labor market experience and subsequent labor market performance using data on all Swedish youths graduating from vocational high schools in the recession years of 1991-94. Sibling fixed-effects combined with detailed data on high school programs, grades and work experience during high school are used in order to identify the causal long-run effects of post-graduation unemployment. The results show significant scarring effects resulting in higher risks of unemployment up to 5 years later. The results imply that poor labor market performance as a teenager result in persistent, but not permanent, negative effects.
urn:nbn:de:101:1-201104133876
Keywords: J64; 330; youth unemployment; scarring; state dependence; siblings; Jugendarbeitslosigkeit; Berufseinstieg; Erwerbsverlauf; Arbeitslosigkeit; Schweden